Komparace současného stavu s požadavky normy ČSN EN ISO 9001 2001 ve firmě Tiskárna Brouček - Vovsová, Zuzana (2008)
The objective of this diploma paper is a comparison of present status of the small firm Tiskárna Brouček with standards ISO 9001. ISO 9001 refers to system of quality management.There are many recommendations to help change some nonconforming activities at the printing shop Tiskárna Brouček.